2010
DOI: 10.1111/j.1600-0587.2009.05975.x
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic community structure in Minnesota oak savanna is influenced by spatial extent and environmental variation

Abstract: The relative importance of environmental filtering, biotic interactions and neutral processes in community assembly remains an openly debated question and one that is increasingly addressed using phylogenetic approaches. Closely related species may occur together more frequently than expected (phylogenetic clustering) if environmental filtering operates on traits with significant phylogenetic signal. Recent studies show that phylogenetic clustering tends to increase with spatial scale, presumably because great… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
144
2
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 127 publications
(155 citation statements)
references
References 83 publications
5
144
2
2
Order By: Relevance
“…These results are consistent with those found in Serengeti plant communities and fern communities in Costa Rica, where there is greater phylogenetic clustering in stressful habitats (Anderson et al 2011, Kluge andKessler 2011). However, environmental gradients do not always lead to changes in phylogenetic community structure (Bryant et al 2008), especially in cases when community assembly is strongly dominated by one assembly process (Willis et al 2010).…”
Section: Introductionsupporting
confidence: 81%
“…These results are consistent with those found in Serengeti plant communities and fern communities in Costa Rica, where there is greater phylogenetic clustering in stressful habitats (Anderson et al 2011, Kluge andKessler 2011). However, environmental gradients do not always lead to changes in phylogenetic community structure (Bryant et al 2008), especially in cases when community assembly is strongly dominated by one assembly process (Willis et al 2010).…”
Section: Introductionsupporting
confidence: 81%
“…the sampled site (Table 2, Table 3 in Appendix 1). Association patterns between phylogenetic clades and some types of habitats are not new in the literature (Swenson et al 2006, Willis et al 2010, Duarte 2011, Kooyman et al 2011, but in this study we observed that the clade-habitat relationships were recurrent across different vegetation types, regardless of the phylogenetic pool size used to evaluate that association. Basal clades (Magnolianae) were associated with forest areas, while clades of more recent diversification (Rosanae and Asteranae) tended to represent the forefront of forest expansion processes over grasslands in different phytogeographic regions in Southern Brazil (Fig.…”
Section: Discussionmentioning
confidence: 64%
“…These results also emphasize that phylogenetic patterns are scale dependent (CavenderBares et al 2006, Willis et al 2010. At our large scale (yards vs. Cedar Creek), the drop in phylogenetic diversity with urbanization was clear; on the small scale (yards along the urban to exurban gradient), there was no clear trend.…”
Section: Phylogenetic Diversity Of Spontaneous Yard Florasmentioning
confidence: 55%